Building maintenance lift and fire protection system at Menara MPSPK, Sungai Petani, Kedah / Ahmad Daniel Faiz Mahadzir - Mahadzir, Ahmad Daniel Faiz (Universiti Teknologi Mara, Perak, 2018)
Practical training is a compulsory subject to all student to finish the Diploma. From the practical training, I can know and learn deeply about the new knowledge that I cannot get from the class about the building industry. From that, I learnt the aspects of organizational management, technology, design, property, communications, project planning and management. I was given exposure to up-to-date process and practices. With this, I will be knowledgeable and experience in handling work in the real situations from the practical training. For our information, all types of report should have their own function and objective. Which that reason, the practical training report have their objective which is: 1. Produce a report and an effective presentation of selected case study and title. 2. Justify the relationship of various professionals and their practices in the building industry as well as the integration and cross subject analysis and synergy. 3. Describe a multi-disciplinary approach to problem solving encountered in a project. 4. Reinforce the wide array of skills, knowledge and applications necessary for the successful completion of project and teamwork. Based on the title that I chose for the report , I should know the specific detail about my case study with following scopes. The detail of property for the case study that we studied such as building background, function, building height and so on. Next, we must study about their organization or maintenance management in the case study. Other than that, I learn about their maintenance work and the function for the lift and fire protection system in details.